Physiological responses to acid stress of an acid-soil tolerant and an acid-soil sensitive strain of Rhizobium leguminosarum biovar trifolii - Watkin, Elizabeth; O'Hara, G.; Glenn, Andrew (Elsevier Science Ltd, 2003)
Physiological responses to acid stress in two strains of Rhizobium leguminosarum bv trifolii of differing acid-soil tolerance were compared. Acidity affected the size and morphology of the acid-tolerant strain, WSM409, but not of the acid-sensitive strain, TA1. Acid grown cells of WSM409 and TA1 had less cell-associated Ca and Mg and more P than cells grown at pH 7.0. Potassium content was lower in acid grown cells; WSM409 was less affected by pH than that in TA1. WSM409 was more tolerant of pH shock at pH 3.5 when grown at pH 4.8 than when grown at pH 7.0. TA1 was more sensitive to pH shock when grown at pH 4.8 than when grown at pH 7.0. WSM409 shows a characteristic adaptive acid tolerance response, whereas TA1 shows an acid sensitive response.